2019
DOI: 10.1038/s41598-019-45100-7
|View full text |Cite
|
Sign up to set email alerts
|

Pax 6 Controls Neural Crest Potential of Limbal Niche Cells to Support Self-Renewal of Limbal Epithelial Stem Cells

Abstract: On ocular surface, corneal epithelial stem cells (SC) reside in limbus between cornea and conjunctiva. Pax6, an evolutionally conserved transcription factor essential for eye development, is expressed in post-natal corneal and limbal epithelia progenitors (LEPC) but not in underlying stroma. Because Pax6 is transiently expressed in developing corneal stroma and a subset of limbal and corneal stromal progenitors, we examined the role of Pax6 in limbal niche cells (LNC) in maintaining the phenotype of neural cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 54 publications
(81 reference statements)
4
31
0
Order By: Relevance
“…CPVL immunopositive cells were found in the limbal stroma next to the limbal basal epithelial cells, with a small minority coexpressing TP63 ( Figure S6B-D). This cluster also showed high expression of PAX6 (Table S1), a transcription factor expressed in the limbal niche cells in the stroma (Chen et al, 2019), whose function is to maintain the phenotype of neural crest progenitors. In view of this, we speculated that cluster 10 may represent the limbal neural crest derived progenitors (LNCPs).…”
Section: Identification Of Epithelial Cell Populationsmentioning
confidence: 93%
“…CPVL immunopositive cells were found in the limbal stroma next to the limbal basal epithelial cells, with a small minority coexpressing TP63 ( Figure S6B-D). This cluster also showed high expression of PAX6 (Table S1), a transcription factor expressed in the limbal niche cells in the stroma (Chen et al, 2019), whose function is to maintain the phenotype of neural crest progenitors. In view of this, we speculated that cluster 10 may represent the limbal neural crest derived progenitors (LNCPs).…”
Section: Identification Of Epithelial Cell Populationsmentioning
confidence: 93%
“…These results extend previous observations supporting a role for LNCs and KITL signalling in maintaining LESCs. 21,22 The above notion is based on multiple observations. First, both in That SOX10 is particularly important for LNC development and function is supported by its wider role in the physiology of neural crest cells.…”
Section: The Development and Maintenance Of Lescs Depends On Inter-mentioning
confidence: 99%
“…LESCs are limbal niche cells (LNCs). [13][14][15][16][17][18][19][20][21] Previous results have shown that LNCs support self-renewal of LESCs, 21 and LNCs transplants prevent LSCD in an alkali burn rabbit model. 22 They likely do this by secreting paracrine factors including KITL, 22 but the detailed mechanisms of KITL regulation in LNCs and how KIT, KITL and its downstream signal pathways are involved are not clearly understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Immuno uorescence characterization of unsegregated cultured limbal cells revealed a marker expression pro le that corresponded, for the very most part, to the pro le expected for LSCs. Speci cally, we detected heterogenous expression of the wellrecognized LSC marker p63 [42] and homogenous expression of PAX6, which has been shown to play a critical role in limbal stem cell fate determination [51][52][53]. The absence of the lament proteins CK3/12, which are, due to their speci c expression in corneal epithelial cells and limbal suprabasal but not basal cells, regarded as markers of corneal epithelial differentiation [17,54,55], indicates that the cultivated LSCs have maintained their undifferentiated nature throughout the expansion process.…”
Section: Discussionmentioning
confidence: 87%